The Ability to Write Short Story Synopses of Grade IX Students of SMP Negeri 3 Tiroang, Pinrang Regency - Nurdiana; Suhartini Khalik; M. Nurzin R. Kasau; Jumiati Lanta (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the development and effectiveness of Google Sites-based learning media for improving junior high school students' literacy skills. The research was conducted in response to the growing need for technology-integrated learning media that can support students' reading and listening literacy while increasing their engagement in classroom learning. A Research and Development (R&D) approach employing the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation, was adopted using a mixed-methods design. The participants included Grade VIII students, Indonesian language teachers, and expert validators. Data were collected through observations, interviews, questionnaires, validation sheets, and literacy achievement tests. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, and N-gain analysis, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the developed Google Sites-based learning media met the criteria of validity, practicality, and effectiveness. Students demonstrated significant improvement in literacy achievement after using the media, while teachers and students responded positively to its usability and learning features. The integration of multimedia resources, interactive assessments, and collaborative activities also contributed to increased learner engagement and independent learning. Therefore, Google Sites-based learning media can serve as an effective and accessible digital learning platform for supporting literacy instruction in junior high schools and promoting the integration of educational technology in language learning.